Pembagian Hak Waris Berdasarkan Hadis Bukhari Muslim Dan Pasal-Pasal Kuhperdata - Intan Sukmawati; Tajul Arifin (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to analyze the division of inheritance rights based on the Hadiths of Bukhari and Muslim and the Articles of the Civil Code; how the division of inheritance rights is viewed in the perspective of the Hadiths of Bukhari and whether it is in accordance with the provisions of the Civil Code. The research method used is document analysis, collecting data from Islamic law and civil law literature and comparing the two. The results show that the division of inheritance rights in the Hadiths of Bukhari emphasizes the principles of equality and justice for heirs, while the Civil Code regulates the division of inheritance rights based on lineage and the number of heirs. So, the division of inheritance rights in the Hadiths of Bukhari emphasizes the principles of equality and justice, while the Civil Code regulates the division of inheritance rights based on lineage and the number of heirs, thus indicating a difference in approach in determining inheritance in the context of Islamic law and civil law in Indonesia.